Molar loss and powder diet leads to memory deficit and modifies the mRNA expression of brain-derived neurotrophic factor in the hippocampus of adult mice. Issue 1 (December 2016) - Takeda, Yosuke; Oue, Hiroshi; Okada, Shinsuke; Kawano, Akira; Koretake, Katsunori; Michikawa, Makoto; Akagawa, Yasumasa; Tsuga, Kazuhiro
Abstract Background It is known that tooth loss is known to be a risk factor for Alzheimer's disease and soft diet feeding induces memory impairment. Recent studies have shown that brain-derived neurotrophic factor (BDNF) is associated with tooth loss or soft diet in young animal model, and that BDNF expression is decreased in patients with Alzheimer's disease. However, single or combined effect of tooth loss and/or soft diet on brain function has not fully understood. Here we examined the effect of molar loss and powder diet on memory ability and the expression of BDNF mRNA in the hippocampus of adult C57BL/6J mice. Twenty eight-weeks-old C57BL/6J mice were divided into intact molar group and extracted molar group. They were randomly divided into the I/S group (Intact upper molar teeth/Solid diet feeding), the E/S group (Extracted upper molar teeth/Solid diet feeding), the I/P group (Intact upper molar teeth/Powder diet feeding), and the E/P group (Extracted upper molar teeth/Powder diet feeding). The observation periods were 4 and 16-week. To analyze the memory ability, the step-through passive avoidance test was conducted. BDNF-related mRNA in the hippocampus was analyzed by real-time polymerase chain reaction (RT-PCR). Results At 4 weeks later, we performed memory test and isolated brains to analyze. There were no differences in memory function and BDNF mRNA level between these four groups. However, at 16 weeks later, E/S and E/P group showed memory impairment, and decreased level of BDNF mRNA. Whereas, the powder diet had no effect on memory function and BDNF mRNA level even at 16 weeks later. Conclusions These results suggest that the effect of molar loss and powder diet on memory function and BDNF mRNA levels were different, molar loss may have a greater long-term effect on memory ability than powder diet does.